2004
DOI: 10.1055/s-2004-835256
|View full text |Cite
|
Sign up to set email alerts
|

Prävalenz funktioneller Beschwerden des Rückens und der Hüft- und Kniegelenke bei Adoleszenten

Abstract: The majority of functional back, hip and knee pain in adolescents must be classified as functional complaints. There is a significant association with female sex, visiting a high school and the consumption of legal drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…We believe that this discrepancy between the lack of association with the outcome and the presence of association in the assessment of functional impairment may be explained by the higher prevalence of symptoms such as edema, crepitation, difficulty in bending, straightening and stiffness, greater difficulty in doing daily living activities, sports, and leisure activities in adolescent girls with knee pain. When investigating knee pain prevalence among 2368 German adolescents, Spahn et al 19 also did not find an association with gender. Nevertheless, knee pain in women may not be a benign condition.…”
Section: Discussionmentioning
confidence: 93%
“…We believe that this discrepancy between the lack of association with the outcome and the presence of association in the assessment of functional impairment may be explained by the higher prevalence of symptoms such as edema, crepitation, difficulty in bending, straightening and stiffness, greater difficulty in doing daily living activities, sports, and leisure activities in adolescent girls with knee pain. When investigating knee pain prevalence among 2368 German adolescents, Spahn et al 19 also did not find an association with gender. Nevertheless, knee pain in women may not be a benign condition.…”
Section: Discussionmentioning
confidence: 93%
“…Studies have found that the prevalence of knee pain is 3.9 % among children and 18.5 % in adolescents [ 28 ]. Some studies have reported an even higher prevalence of pathological knee pain in adolescents, with a range from 28.5 to 31 % [ 35 , 36 ]. Knee pain in early life can result from many conditions that are not related to OA in later life.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, a substantial portion of children also attributed cause of pain to noise, school transfer, death of a relative, relocation of residence and divorce of parents (Table 5). These negative events, despite their questionable value as real contributing factors, might induce stress and further lead to a mental suffering or psychosomatic pain presented as ‘headache’ (Larsson, 1988; Laurell et al, 2005; Tyrer, 2006; Hjern et al, 2008) or other functional pain such as abdominal pain (Spahn et al, 2004). Over two‐thirds of the MBP occurred repeatedly and started 3 months prior, suggesting a chronic pain condition.…”
Section: Discussionmentioning
confidence: 99%